2007
DOI: 10.1002/ls.48
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Newtonian and thermal effects in constant flow valve compensated symmetric hole‐entry hybrid journal bearing

Abstract: Every high speed machine, demanding high level of perfection, can operate successfully through a precise design of bearings. Such a design can be formulated after carefully studying both static and dynamic characteristics of the journal bearing. The present paper described the study of static and dynamic performance of a hole-entry hybrid journal bearing system compensated with constant fl ow valve restrictor by considering the combined infl uence of thermal effects and non-Newtonian behaviour of the lubricant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Garg et al, [7] presented a comprehensive review of the developments in the design and application of hydrostatic and hybrid journal bearing systems and concluded that more extensive research is needed, both analytical as well as experimental, to consider the extension of these bearings into highspeed applications. Garg et al, [8] found that change in viscosity of lubricant due to non-Newtonian behavior and rise of temperature affects the performance of the constant flow valve-compensated hole-entry hybrid journal bearing system quite significantly. Garg et al, [9] studied the performance of a capillary-compensated hole-entry journal bearing system and found that the value of minimum fluid-film thickness ( h min ) reduces due to the decrease in viscosity because of consideration of thermal effects and the non-Newtonian behavior of the lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al, [7] presented a comprehensive review of the developments in the design and application of hydrostatic and hybrid journal bearing systems and concluded that more extensive research is needed, both analytical as well as experimental, to consider the extension of these bearings into highspeed applications. Garg et al, [8] found that change in viscosity of lubricant due to non-Newtonian behavior and rise of temperature affects the performance of the constant flow valve-compensated hole-entry hybrid journal bearing system quite significantly. Garg et al, [9] studied the performance of a capillary-compensated hole-entry journal bearing system and found that the value of minimum fluid-film thickness ( h min ) reduces due to the decrease in viscosity because of consideration of thermal effects and the non-Newtonian behavior of the lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effect of flexibility in bearing and temperature variations in the lubricant was considered in the analysis of hybrid journal bearings 13 compensated with constant flow valve. Thermohydrostatic analysis of the hybrid journal bearings compensated with constant valve 14 and capillary restrictor 15 was performed with the non-Newtonian lubricant. A comparison in the analysis of slot and hole entry hybrid bearings was performed by Garg et al 16 by considering the thermal effects and non-Newtonian lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…The different lubricants considered in these bearings were sodium, 6 water, 7 cryogenic liquid, 8 and electrorheological fluid. 9 Some of the properties of the lubricant considered in the bearing analysis are turbulence, 10 inertia, 11 compressibility, 12 shear stress, 13 and microstructures. 14 The microstructures are present in the lubricant due to its mineral nature and the blended additives.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effect of flexibility in bearing and temperature variations in lubricant was considered in the analysis of hybrid bearing 23 compensated with constant flow valve. Thermohydrostatic analysis of hybrid bearing compensated with constant valve 13 and capillary restrictor 24 was performed with non-Newtonian lubricant. A comparison in the analysis of slot and hole entry hybrid bearings was performed by Garg et al 25 by considering thermal effects and non-Newtonian lubricant.…”
Section: Introductionmentioning
confidence: 99%